Hubungan antara Perilaku Prososial dan Psychological Well-Being pada Remaja Awal - Marbun, Rodelina; Setiawan, Jenny Lukito (Psychopreneur Journal, 2019)
This research has a goal to know the relationship between prosocial behavior and psychological well-being on early adolescence. This research is using correlational design. Population and sample are junior high school X’s students in Surabaya. The sampling technique uses total population study. There are 153 samples in this research. Data collection uses a scale consisting of a scale of prosocial behavior and psychological well-being scale. The scale of prosocial behavior is adapted from the scale developed by Caprara and Steca (2007), while scale of psychological well-being adapted from the scale developed by Ryff (1989). Pearson Product Moment correlation test results showed that there was a positive correlation between prosocial behavior and psychological well-being in early adolescence (r = 0,299; p <0,05). The more early adolescence perform prosocial behavior the better their psychological well-being.